ANALYSIS OF FINANCIAL FEASIBILITY OF GOAT BUSINESS CUT AS A FAMILY BUSINESS KATANGKA SUB-DISTRICT SOMBA OPU, GOWA DISTRICT - Maisyaroh, Ummi; Anwar; Amin, Andi Mustika; Ramli, Anwar; Nurman (Journal Management & Economics Review (JUMPER), 2023)
The purpose of this study was to analyze the financial feasibility of beef goat business as a family business in the Katangka Village, Somba Opu District, Gowa Regency. This type of research is a descriptive study with a quantitative approach, population and sample in this study business actors in the business of slaughtered goats in the Katangka Village, Somba Opu District, Gowa Regency. The results showed that the goat business that was run in the Katangka Village, Somba Opu District, Gowa Regency from the financial feasibility analysis was declared feasible and had economic benefits, as evidenced by the results of calculating the NVP value indicating that NVP> 0.